Program Desa Membangun di Desa Tamaila - Yayu Indriati Arifin; Irvin Novita Arifin (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
Tamaila Village is one of the villages located in Tolangohula District, Gorontalo Regency, Gorontalo Province, astronomically located at the coordinates of N 0044'27.9 "E 122º28'42.18". The method of implementing the program carried out by KKN students is the thematic village building. The program carried out by the Thematic KKN students is divided into several programs that are beneficial to the community in Tamaila village. Such as conducting socialization of vaccinations, making latrines and building boundaries in five hamlets in Tamaila village, then doing morning exercises with village officials and kindergarten children, planting sensifera, helping flood-affected residents in Karya Jaya hamlet, Tamaila village, data collection on dasa wisma in tamaila village, clean friday, maintenance of sports facilities and infrastructure and teaching kindergarten children about healthy lifestyles. This program is expected to be useful for the community.